THE STUDY ON TOURISM BEHAVIOR AND ATTITUDE TOWARDS PURCHASING OUTBOUND TOURISM PACKAGES IN ASIA - PASIFIC AMONG CONSUMERS IN BANGKOK AND OUTSKIRTS OF BANGKOK - Boonchuay, Krissanabhat (Academic Journal of Thailand National Sports University, 2024)
The research aimed to study demographic characteristics in purchasing outbound tourism packages in Asia - Pacific among consumers in Bangkok and outskirts of Bangkok, to study outbound travel behavior in Asia - Pacific among consumers purchasing outbound tourism packages in Asia - Pacific, and to study attitude towards purchasing outbound tourism packages in Asia - Pacific. The research was conducted on the basis of survey research design. Data were collected from 400 copies of the questionnaire. Index of item - objective congruence (IOC) was used to measure the quality of the questionnaire and it was found that each item had IOC greater than 0.50. Therefore, the questionnaire was workable. The reliability of the questionnaire was 0.81. The research results indicated that the majority of consumers in Bangkok and outskirts of Bangkok who purchased outbound tourism packages in Asia-Pacific were women. Most of them were 40-49 years old, were single, graduated with a bachelor’s degree, were company employees and had monthly income 15,001 - 30,000 baht. With regard to outbound travel behavior in Asia - Pacific among consumers purchasing outbound tourism packages in Asia - Pacific, most respondents purchased the packages from tourist destination reputation. Besides, it was found that most of them spent 2 - 5 days travelling. In relation to consumers’ attitude towards purchasing outbound tourism packages in Asia - Pacific, most of them had an attitude towards modern tourist destinations at a highest level, the mean was 4.64. With regard to price affecting the purchase of outbound tourism packages in Asia - Pacific, most of them were interested in services and convenience provided to tourists at the highest level, the mean was 4.88. In terms of resources affecting the purchase of outbound tourism packages in Asia - Pacific, most of them were interested in selecting staff who provided services politely and had good human relations at the highest level, the means were 4.88.